Understanding the strategies of venture capital investors in helping their portfolio firms to become international - Terttu Luukkonen (The Research Institute of the Finnish Economy (ETLA), 2007)
This paper reports the findings of two empirical studies on the value-added of venture capital with special attention on promoting internationalisation of start-up firms. The first study is based on a survey of Finnish (and a few cross-border) venture capital organisations on the value-adding mechanisms they use with regard to their portfolio firms. The second study is based on interviews with Finnish biotechnology start-ups. Attention is paid specifically to the strategies of three different types of investors in early-stage high growth companies: 1) business angels, which can be regarded as informal venture capitalists, 2) private-sector venture capital firms and 3) public-sector venture capital organisations. Control of agency costs and risks provides a conceptual framework for analysing the strategies of the different investor types. The findings partially corroborate and partially refute the hypotheses made on the basis of theory and the two studies provide somewhat conflicting findings on the role and strategies of the different investor types. According to the venture capital survey, private sector venture capital firms were most actively engaged in ex post monitoring and `coaching' of their portfolio firms in internationalisation, while according to the biotechnology study, business angels turned out to be most actively engaged. The paper discusses potential reasons for these divergent findings.
Keywords: G24; O16; 330; venture capital; internationalisation of start-ups; Risikokapital; Strategisches Management; Erfolgsfaktor; Unternehmensentwicklung; Multinationales Unternehmen; Finnland